+0  
 
0
720
2
avatar+598 

Find the maximum value of $y/x$ over all real numbers $x$ and $y$ that satisfy \[(x - 3)^2 + (y - 3)^2 = 6.\]

 Oct 30, 2017
 #1
avatar+95883 
+2

 (x - 3)^2 + (y - 3)^2 = 6

 

This is a circle with a center of  (3, 3)    and a radius  = √ 6

 

I don't know how to prove this but WolframAlpha gives the answer as

 

{ x , y }  =  ( 2 - √ 2 , 2 + √ 2 )

 

And   y / x   ≈   [ 2 + √ 2 ]  / [ 2  - √ 2 ]  ≈  5.828

 

 

cool cool cool

 Oct 31, 2017
 #2
avatar+95883 
+2

Here's the   Calculus solution for this one...it's a little difficult  !!!

 

 (x - 3)^2 + (y - 3)^2 = 6

 

(y - 3)^2  =  6 -  [ x^2 - 6x + 9]

 

( y - 3)^2  =  6x- x^2 - 3

 

y - 3  = √ [ 6x- x^2 - 3] 

 

y = √ [ 6x- x^2 - 3]  + 3

 

So......call y/x  =  z  ....so we have

 

z =  y/x  =   [ √ [ 6x- x^2 - 3]  + 3]  / x

 

The derivative  of this is messy, but we have

 

z'  =   - 3 ( x  + √ [ 6x- x^2 - 3] - 1 )  /   [ x^2 * √ [ 6x- x^2 - 3] ]

 

We  can find a solution that minimizes  x   by  solving   this :

 

( x  + √ [ 6x- x^2 - 3] - 1 )  =  0

 

x - 1  =   -√ [ 6x- x^2 - 3]        square both sides

 

x^2 - 2x + 1  =  6x- x^2 - 3

 

2x^2 - 8x + 4  =  0

 

x^2 - 4x + 2  = 0

 

The solution that minimizes x  is      2 - √ 2

 

And using    (x - 3)^2 + (y - 3)^2 = 6    

 

When  x =  2 - √ 2     we have

 

( 2 - √ 2 - 3 )^2 +  (y - 3)^2 = 6

 

( 1 + √ 2)^2 +  (y - 3)^2 = 6

 

1 + 2 + 2√ 2 + (y - 3)^2 = 6

 

 (y - 3)^2 = 3 -  2√ 2

 

y =  √ [ 3 -  2√ 2] + 3    ⇒ √  [ ( 1 -√2  ) ^2 ]  + 3   or √  [ ( √2 - 1 ) ^2 ]  + 3  ⇒   

 

y =  4 - √ 2     or   y =   2 + √ 2

 

And   

 

[  2 + √ 2 ] / [  2 - √ 2 ]   maximizes  y / x

 

 

cool cool cool

 Nov 1, 2017

13 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.